American sketches great leaders, creative thinkers, and heroes of a hurricane - Isaacson, Walter (New York Simon & Schuster, 2009)
In this collection of essays, the brilliant, acclaimed biographer Walter Isaacson reflects on lessons to be learned from Benjamin Franklin, Albert Einstein, Bill Gates, Henry Kissinger, Ronald Reagan and Mikhail Gorbachev, Hillary Clinton and Bill Clinton, and other interesting characters he has chronicled both as biographer and journalist. He writes also about how he became a writer, the challenges for journalism in the digital age, and offers loving tributes to his hometown of New Orleans.
Includes bibliographical references and index.
Keywords: Isaacson, Walter